Αξιολόγηση της υπηρεσίας οικοσυστήματος της βιολογικής αντιμετώπισης σε συμβατικές καλλιέργειες τομάτας - Δημητριάδης, Δημήτριος (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
Natural predators provide an invaluable service to an ecosystem, that of biological control. Crop margins provide important refugees to natural enemies and may improve biological control within the crop. The current study aimed at evaluating the ecosystem service of predation in Mediterranean tomato crops. Evaluation of predation within and in the margins of tomato fields was carried out in Pafos and Limassol during two periods: the fall-winter and the spring crop using Ephestia kuehniella eggs as prey facsimiles. The facsimiles were placed within the tomato crop and on wild plants on field margins. A week later, predation was assessed by counting the number of missing eggs. Results showed that predation in the field margins was five times lower than predation within the tomato crop. Beat sampling identified Nesidiocoris tenuis as the only predator present on tomato plants, and only during the spring season. Diversification of tomato fields using native plant species may increase the ecosystem service of predation and reduce the need for chemical pesticide applications.
Keywords: Ecosystem; Nesidiocoris tenuis; Tomato; Crop; Ephestia kuehniella; Οικοσύστημα; Καλλιέργεια; Ντομάτα